Cell agglomeration in the wells of a 24-well plate using acoustic streaming. Issue 5 (10th February 2017) - Kurashina, Yuta; Takemura, Kenjiro; Friend, James
Abstract : Cell agglomeration is essential both to the success of drug testing and to the development of tissue engineering. Abstract : Cell agglomeration is essential both to the success of drug testing and to the development of tissue engineering. Here, a MHz-order acoustic wave is used to generate acoustic streaming in the wells of a 24-well plate to drive particle and cell agglomeration. Acoustic streaming is known to manipulate particles in microfluidic devices, and even provide concentration in sessile droplets, but concentration of particles or cells in individual wells has never been shown, principally due to the drag present along the periphery of the fluid in such a well. The agglomeration time for a range of particle sizes suggests that shear-induced migration plays an important role in the agglomeration process. Particles with a diameter of 45 μm agglomerated into a suspended pellet under exposure to 2.134 MHz acoustic waves at 1.5 W in 30 s. Additionally, BT-474 cells also agglomerated as adherent masses at the center bottom of the wells of tissue-culture treated 24-well plates. By switching to low cell binding 24-well plates, the BT-474 cells formed suspended agglomerations that appeared to be spheroids, fully fifteen times larger than any cell agglomerates without the acoustic streaming. In either case, the viability and proliferation of the cells were maintained despite acoustic irradiation and streaming. Intermittent excitation was effective in avoiding temperature excursions, consuming only 75 mW per well on average, presenting a convenient means to form fully three-dimensional cellular masses potentially useful for tissue, cancer, and drug research.